2005
DOI: 10.1111/j.1467-9655.2005.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

The Literary Image of Anthropologists*

Abstract: Strangely, anthropologists have ignored popular accounts of themselves. Yet anthropologists are the most popularized academics in fiction. They are portrayed as either heroic or (much more common) pathetic. Fieldwork marks them out as distinctive and makes ordinary anthropologists odd and the already odd ones even odder. Writers of fiction exploit these characters to enable geographical shifts, debate cultural relativity, poke fun at the discipline, discuss anthropological ideas, and detect crimes. Usually, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…The ethnographer, the artist, throw themselves in the crowds voluntarily, heroically, alone, following Malinowski's epics. But the heroic figure of the gentleman flȃneur/artist/ethnographer can be misleading: the walking ethnographer/ artist is a vulnerable figure (McClancy 2005), who can easily fall in her/his own trap.…”
Section: A R T a N D W A L K I N G U T O P I A Smentioning
confidence: 99%
“…The ethnographer, the artist, throw themselves in the crowds voluntarily, heroically, alone, following Malinowski's epics. But the heroic figure of the gentleman flȃneur/artist/ethnographer can be misleading: the walking ethnographer/ artist is a vulnerable figure (McClancy 2005), who can easily fall in her/his own trap.…”
Section: A R T a N D W A L K I N G U T O P I A Smentioning
confidence: 99%
“…A 2005 article from American Anthropologist examines perceptions of that profession by drawing on a study of fifty‐three films (more than half of which are horror films). An article in The Journal of the Royal Anthropological Institute from that same year looked at one hundred and seventy works of fiction and found that anthropologists are depicted either as “heroic” or “pathetic,” with far more of the latter (MacClancy , 551). Anthropologists have the distinct advantage, though, of being located in anthropology departments in popular culture and real life, making them easier to track down in both.…”
Section: Who Studies Religion According To Popular Culture?mentioning
confidence: 99%
“…Mi smo egzotični kod kuće, dvorske lude akademije, identifikovani s našim stigmatizovanim, trivijalizovanim predmetima proučavanja širom sveta, siromašnim, ne-belim, seksualnim manjinama u svakoj državi di Leonardo 1999prema Chalfen 2003 Bez obzira na činjenicu da javni imidž i identitet discipline direktno utiče na finansiranje istraživanja i na mogućnost zaposlenja diplomiranih antropologa (Shore 1996, 4), antropolozi su relativno kasno uočili značaj proučavanja popularnih reprezentacija sopstvene profesije u masovnoj kulturi (o predstavljanju antropologa u štampanim medijima v. Gusterson 2013). Predstave o disciplini i načini na koji se antropolozi portretišu u različitim žanrovima popularne kulure tek od prve polovine dvehiljaditih godina postaju tema antropoloških istraži-vanja (Chalfen 2003;MacClancy 2005;Salamone 2012;Weston et al 2015). Meklensi napominje da su antropolozi ignorisali popularne predstave o svojoj profesiji bez obzira na činjenicu da oni predstavljaju najpopularnije ili najpopularizovanije naučnike u fikciji (MacClancy 2005, 550).…”
Section: Uvodunclassified